LEGAL MEMORANDUM: A BAN ON SMOKING IN FEDERAL BUILDINGS IS NOT REQUIRED TO ADDRESS LIABILITY CONCERNS (Tufts Archival Research Center, 2007)
Report discussing a proposed ban on smoking in all federal buildings. Expresses concern that the restriction protects non-smokers more than is necessary and is unwarranted in respect to federal liability of smoking in the workplace. Discusses a report by the Environmental Protection Agency (EPA) which classifies tobacco smoke as a carcinogen and states that it causes lung cancer. Explains that banning smoking would do little to improve air quality.